If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x * x + -5x + 4 = 0 Multiply x * x x2 + -5x + 4 = 0 Reorder the terms: 4 + -5x + x2 = 0 Solving 4 + -5x + x2 = 0 Solving for variable 'x'. Factor a trinomial. (1 + -1x)(4 + -1x) = 0Subproblem 1
Set the factor '(1 + -1x)' equal to zero and attempt to solve: Simplifying 1 + -1x = 0 Solving 1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -1x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + -1x = 0 + -1 -1x = 0 + -1 Combine like terms: 0 + -1 = -1 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {1, 4}
| 9m+3=15 | | 1/2-3=2 | | -18/1=9-a/2 | | -2/5r=-4 | | 1. 10x+5(x-4)=7x | | 1. 10x+5(x-4)=7x+4(x-9) | | x*x+5x-50= | | (x+7)(x-2)=(x+1)squared | | 3/10(340) | | 3/10(260) | | 9x+26+7x-17=2x+9(-3x)+5x | | 2a-4+5a-6= | | (15+n)-4=28 | | 8.58=(8p)/2 | | 0.2x-0.5x=0.1x+8 | | x*x+7x+10= | | (7.4X)+(1/5X)-(3/2)=(4/5X) | | 2xsquared+3x-15=0 | | 4.5(x-8)=13.5 | | 20=4xw | | (7/4)+(1/5)x-(3/2)=(4/5)x | | 2/5y+3=-3/5y | | 0=w^2+5w-456 | | r+3t=s | | 11+I=14 | | 2x^2+16-18=54 | | 2/5b=-4 | | 3t+r=s | | Y=9-5(2) | | 2x^2+16-18=0 | | X/10=-8/5 | | 4-p-p-p-p+2p= |